Uma análise da atuação dos bancos no Brasil, o papel do crédito no desenvolvimento local - Luz, Alan Andrade (2009)
As a matter of fact the well succeeded local experiences are due to public policies leading to credit support for business-related to priority productive chains and/or by creating regulation marks for the development of local economy. On the other hand, there have also been independent initiatives that worked out well such as the creation of social coins or Community banks. Nevertheless, the private banks are recquired in order to participate in that process which perhaps may be reached by finding out solutions for risk sharing in credit (by establishing alternative safeguards procedures) and taking part in local savings reinvestment in productive activity. Whether well articulated, those kinds of actions will certainly strength the impact of the credit in the sustainable and balanced local development. Therefore, a more equitable local distribution of bank credit, including the participation of all financial actors, will certainly contribute to reduce the regional development inequalities in the country. The goal of this work is to demonstrate the fundamental character of credit for local development, particularly the role of financial agents whose responsibility is to promote the stimulating and energizing of the economy. However, such actions must be highly connected to the interaction among civil society organizations, the local authorities and local companies in searching of an effective social management of the territory. The theme approaching has involved the review of theories and concepts concerning local development, ethics and social management. Then, there has been a research on existing strategies which facilitate access to credit. The data were collected from various sources such as reports of BACEN, FEBRABAN, BB, BNB, INSTITUTO CIDADANIA, INSTITUTO POLIS, IDEC, FGV-CES, besides a personal interview applied to a manager of BNB